2003
DOI: 10.1002/pen.10021
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the rheological and mechanical properties of a polystyrene‐polyisobutylene‐polystyrene triblock copolymer and its blends with polystyrene

Abstract: The rheological and mechanical properties of a polystyrene‐polyisobutylene‐polystyrene (SIBS) block copolymer containing 30 wt% polystyrene (PS) and its blends with PS (SIBS/PS) were investigated. Atomic Force Microscopy (AFM) was used to visualize the nanostructured phase morphology of the SIBS, which is responsible for the mechanical strength of this thermoplastic rubber. The order‐disorder transition (ODT) for the SIBS block copolymer was found to be above 250°C. SIBS/PS blends with 10–30 wt% PS showed impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 19 publications
2
22
0
Order By: Relevance
“…As described above, PIB is the main component of the thermoplastic elastomer SIBS, [40][41][42] which is used in combination with PTX as the coating material on the clinical TAXUS TM 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 5 stent. 43,44 PTX is widely used in anticancer treatment, but because of its potent anti-mitotic activity, 45,46 it is also an excellent anti-proliferative for use with cardiovascular stents.…”
mentioning
confidence: 99%
“…As described above, PIB is the main component of the thermoplastic elastomer SIBS, [40][41][42] which is used in combination with PTX as the coating material on the clinical TAXUS TM 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 5 stent. 43,44 PTX is widely used in anticancer treatment, but because of its potent anti-mitotic activity, 45,46 it is also an excellent anti-proliferative for use with cardiovascular stents.…”
mentioning
confidence: 99%
“…It can therefore be concluded that all results in this study are computed for realistic ranges of interface strengths and for commercially relevant polymer coating materials. 3,4,31 We are currently performing a series of mixed mode experimental tests to determine interface properties for polymer coatings on stainless steel substrates, allowing for the precise measurement of s max and r max .…”
Section: Discussionmentioning
confidence: 99%
“…Blends of PC are used on Medtronic and Abbott Vascular stent systems. Hyperelastic materials' behavior with properties being based on published stress-strain test data is assumed for Chronoflex, 3 SIBS, 4 and PU-GPC. 31 Strain rate-dependent data have not been published for these materials and are therefore not considered in this study.…”
Section: Finite-element Modelmentioning
confidence: 99%
“…Reported tensile strength of this specific SIBS formulation, for example, ranges from 12.7 MPa to 17.7 MPa [13,31]. In the work by Lim et al, the use of nanofillers was investigated in order to improve mechanical properties of compression-molded SIBS, though no consideration was given to the effect of process parameters.…”
Section: Artificial Neural Networkmentioning
confidence: 97%